The Influence of Work Placement, Work Stress and Teamwork on the Performance of Aviation Security Personnel of PT Angkasa Pura I Yogyakarta International Airport (YIA) Branch - Mirnawati, Mirnawati; Santosa, Awan (CV. Rayyan Dwi Bharata, 2024)
This research aims to determine the effect of work placement, work stress and teamwork on the performance of Aviation Security personnel at PT Angkasa Pura I Yogyakarta International Airport (YIA) Branch. The population in this study were all employees of PT Angkasa Pura I Yogyakarta International Airport (YIA) Branch who worked at the terminal with a total of 240 people. In calculating the Slovin formula, a sample of 36 people was obtained. The data analysis used is descriptive statistics, multiple linear regression, coefficient of determination (R²) and partial hypothesis testing (t test). The results of this research show that good work placement and teamwork have a positive and significant influence on employee performance, while work stress has no effect on employee performance. In conclusion, to improve the performance of security personnel, management needs to pay attention to appropriate work placement, reduce work stress through employee support programs and strengthen teamwork.